Epidemiologia de candidíase hospitalar: Importância da identificação específica - Miranda, E. T. [UNESP]; Silva, R. A. M. [UNESP]; Fusco-Almeida, A. M. [UNESP]; Melhem, M. C. S.; Pukinskas, S. R. B. S.; Mendes Giannini, Maria José Soares [UNESP] (My University, 2003)
Nosocomial infections with Candida species are recognized as a significant cause of morbidity and mortality in both seriously ill immunocompetent and immunocompromised patients. Infections with Candida albicans and non-albicans Candida species have become a significant cause of infection in humans. Several of the more commonly Candida spp isolates are less susceptible to the antifungal drugs currentlly applied in clinical treatment, a factor that means significant difficulties for effective treatment. The modern mycology laboratory has an important role to play in several aspects relating to these organisms, including therapy, detection, identification and epidemiological analysis. In this study, we have provided an initial comparison of differences in species distribution among Candida isolates from four general hospitals of São Paulo,SP. Overall, 40 isolates of C. albicans, C. parapsilosis and C. tropicalis were isolated respectively in 35%, 50% and 15%, revealed a tendency of higher frequency of non-albicans species. The species distribution in patients with candidemia showed that the most commonly species were C. parapsilosis (45,4%), followed by C. albicans (36,4%) and C. tropicalis (18,2%); thus, we have an increase of non-albicans species. The three different species were include in 6, 3, and 4 different biotypes, respectively C. albicans, C. parapsilosis e C. tropicalis. This study emphasizes the importance of periodic evaluation of Candida species distribution especially in centers caring for patients at risk.
Epidemiology of nosocomial candidiasis: The importance of specific identification
Keywords: Candida; Epidemiology; Nosocomial infections; antifungal agent; Brazil; Candida albicans; Candida parapsilosis; Candida tropicalis; candidiasis; comparative study; epidemiological data; fungal detection; fungus identification; fungus isolation; general hospital; high risk patient; hospital infection; morbidity; mortality; mycosis; patient care; species distribution